Brilliant coaching : how to be a brilliant coach in your workplace - Starr, Julie (Harlow, Ennmn 4/06/13gland ; New York : Pearson/Prentice Hall, 2008)
Brilliant coaching shows how anyone can be a brilliant coach at work. Based on methods specifically developed and proven in business, you’ll discover what it takes to be a coach, how to use the core coaching methods and how to apply these to common coaching scenarios. With brilliant coaching you’ll unlock your own unique coaching ability and reap the rewards in no time.
What is coaching? -- What does it mean to be a manager and coach? -- How does our ego limit our ability to coach? -- Building rapport or relationship -- Focused listening -- Effective questioning -- Constructive feedback -- Off-line : when the coachee has the topic or agenda -- Off-line : when the manager has the topic or agenda -- Off-line : when both the coachee and the manager -- Have things to discuss -- On-line : response coaching -- Taking your learning forward.
Includes index.
nmn 4/06/13
Loans
Keywords: Employees -- Coaching of; Employee motivation; Management